THE INFLUENCE OF THE PROBLEM BASED LEARNING (PBL) LEARNING MODEL ON STUDENT LEARNING OUTCOMES ON ENVIRONMENTAL POLLUTION MATERIAL AT SMPN 1 SAMADUA ACEH SELATAN - Mauizah Hasanah; Anita Safriani; Fatemah Rosma (Jurnal Biologi Sains dan Kependidikan, 2024)
This research is entitled: "The Influence of the Problem Based Learning (PBL) Learning Model on Student Learning Outcomes on Environmental Pollution Material at SMPN 1 Samadua Aceh Selatan", this research aims to find out how the Problem Based Learning (PBL) Learning Model influence the results. Student Learning on Environmental Pollution Material at SMPN 1 Samadua. The data collection technique uses learning outcomes tests and questionnaires. Learning outcomes data are processed using t-test statistics, while student emotional intelligence questionnaires were processed using percentage formulas. The learning outcomes of students in class VII-2 experimental were higher than those in control class VII-1, as a result of data analysis carried out by the author, it was found that the comparison between the t-count values was greater than t-table, namely 10.5 1.68.  This shows that the use of the problem based learning (PBL) learning model in environmental pollution material can influence student learning outcomes at SMPN 1 Samadua, South Aceh.